221k views
3 votes
Determine the zeros of the function
5) y=-x² + 2x + 1

2 Answers

1 vote

zeros of the function y=
-x^2 + 2x + 1 is
x = 1- \sqrt {2} &
x = 1 + \sqrt {2}

Explanation:

Here we have , y=
-x^2 + 2x + 1 in order to find zeros of this quadratic function we get:
-x^2 + 2x + 1 = 0


-x^2 + 2x + 1 = 0


x=\frac{-b \mp \sqrt{\left(b^(2)-4 a c\right.})}{2 a}


x = (-(2) \mp √(2^2-4(-1)(1)) )/(2(-1))


x = (-2 \mp √(4+4)) )/(-2)


x = (-2 \mp √(8) )/(-2)


x = 1 \mp ( √(8) )/(2)

Since, we have two root one with positive & other with negative sign so :


x = 1+ (2 √(2) )/(2)

Therefore, zeros of the function y=
-x^2 + 2x + 1 is
x = 1- \sqrt {2} &
x = 1+ \sqrt {2} .

User CalloRico
by
4.6k points
4 votes

Zeros of function are
x = 1 + √(2) \text{ and } x = 1 - √(2)

Solution:

We have to find the zeros of the function


y = -x^2 + 2x+1

Find the zeros of function:


-x^2 + 2x+1 = 0\\\\\mathrm{For\:a\:quadratic\:equation\:of\:the\:form\:}ax^2+bx+c=0\mathrm{\:the\:solutions\:are\:}\\\\x=(-b\pm √(b^2-4ac))/(2a)


\mathrm{For\:}\quad a=-1,\:b=2,\:c=1\\\\x =(-2\pm √(2^2-4\left(-1\right)1))/(2\left(-1\right))


Simplify\\\\x=(-2 \pm √(4+4))/(-2)\\\\x =(-2 \pm √(8))/(-2)\\\\Simplify\\\\x =(-2 \pm 2 √(2))/(-2)\\\\x = 1 \pm √(2)

We have two zeros


x = 1 + √(2) \text{ and } x = 1 - √(2)

Thus zeros of function are
x = 1 + √(2) \text{ and } x = 1 - √(2)

User Sean Werkema
by
4.6k points